Lactobacillus plantarum KLDS1.0318 Ameliorates Impaired Intestinal Immunity and Metabolic Disorders in Cyclophosphamide-Treated Mice - Meng, Yueyue; Wang, Jing; Wang, Zhiyu; Zhang, Guofang; Liu, Libo; Huo, Guicheng; Li, Chun (Frontiers in Microbiology, 2019)
Cyclophosphamide (CTX), a clinically important antineoplastic drug, also leads to some side effects such as nausea, vomiting and diarrhea in the consumer. In this study, Lactobacillus plantarum (L. plantarum) KLDS1.0318 preserved in our laboratory was orally given to cyclophosphamide-treated mice to explore its potential effects to attenuate CTX-induced toxic effects by modulating intestinal immune response, promoting intestinal integrity and improving metabolic profile. BALB/c mice were randomly divided into six groups including normal control (NC) group, model control (MC) group, immunosuppression plus L. plantarum KLDS1.0318 groups with three different doses (KLDS1.0318-L, KLDS1.0318-M, and KLDS1.0318-H), and plus levamisole hydrochloride as positive control (PC) group. After 20 days, the small intestine the colonic contents were collected for different analyses. The results revealed that the levels of cytokines secreted by Th1 cells and Th2 cells in probiotic treatment groups were significantly higher than those in the MC group. Histopathological results showed that L.plantarum KLDS1.0318 favorably recovered CTX-induced abnormal intestinal morphology by improving villus height and crypt depth as well as quantity of goblet cells and mucins production. Compared to CTX alone-treated group, the production of short-chain fatty acids (SCFAs) were significantly increased and the levels of pH and ammonia were significantly decreased with L.plantarum KLDS1.0318 supplementation. The present study is of clinical relevance and particularly, application of L.plantarum KLDS1.0318 as a unique therapy or in combination to ameliorate the CTX side effects in cancer patients.